Феномен “звезды” в современной массовой культуре (функциональный анализ) - Рязанова, Л. (Социология: теория, методы, маркетинг, 2006)
Solving research problem the author discusses a subject of mass culture. Popular art as the most essential part of mass culture exists side by side with the elitist one as well as plays a broad spectrum of social roles. Functional analysis of popular art shows that it is a symbolical form of world acquisition, the way of understanding and structuring individual and social experience. In this socio -cultural context the “star” symbolically dominates in a cultural space through the transmission of personal values, preferences as well as his/her own “brand”, in a way transforming to a cultural icon and demonstrating high level of social aspirations. The whole “star’s” potential and its impact on social processes have been displayed during the “Orange Revolution”.